Salt-Wasting Congenital Adrenal Hyperplasia in A 2-Year-Old Patient - Nanda Amelia; Tenri Esa; Liong Boy Kurniawan; Ratna Dewi Artati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Congenital Adrenal Hyperplasia (CAH) is an autosomal recessive disorder due to deficiencies of enzymes involved in steroidogenesis in the adrenal cortex. It is known that 90% of CAH are due to 21-hydroxylase enzyme deficiency caused by mutation of the CYP21A2 gene. A female patient aged two years and one month old was reported with a diagnosis of salt-wasting CAH. The diagnosis was based on complaints of genital enlargement since birth. The patient had developed repeated vomiting and severe dehydration since newborn. The patient was diagnosed with CAH and under treatment with glucocorticoid replacement therapy by a pediatrician since the age of 5 months. Body height/age < -3 Standard Deviation (SD) of the Z-score chart (very short stature) and ambiguous genitalia were reported. Laboratory tests indicated thrombocytosis (795x103/uL), mild hyperkalemia (5.4 mmol/L), and increased testosterone (110.1 ng/dL). Bone age study affirmed an advanced bone age. History of increased 17-hydroxyprogesterone (109.19 ng/mL) and decreased morning serum cortisol levels (1.7 ug/dL). History of gynecological ultrasonography (USG) showed uterus, no bilateral testicular structure, hyperplasia of the left adrenal gland, and suggestive of genital ambiguity. The 21-hydroxylase deficiency causes a decrease in aldosterone and cortisol and an increase in androgens. Hypoaldosteronism causes hypovolemia, hyponatremia and hyperkalemia. Hypocortisolime causes hypoglycemia, decreased response to infection, and stress. Hyperandrogenism causes virilization of the genitalia and short stature in patients. A female patient aged two years and one month old was reported with a salt-wasting congenital adrenal hyperplasia diagnosis. Chromosome analysis was the recommended test in this case.